Basel III Regulation and Its Impact on Chinese Commercial Banks Performance - Wan, Maben (2016)
The global financial crisis of 2008 has underlined the importance of bank’s sound liquidity management. As a response, the Basel Committees introduced an upgraded Basel Accord known as “Basel III” with the aim of making the financial system more stable and resilient. In this study, we examine how the standards of Basel III and other financial determinants affect banking profitability and stability. We use a panel data comprised of 50 commercial banks in China over a period of after crisis (2010-2015), approximately 300 observations in the regressions, and applying a dynamic regression model called two-step generalized method of moments (GMM). The empirical evidence suggests that the two variables from Basel III regulation, namely, the capital adequacy ratio (CAR) and the net stable funding ratio (NSFR) are all shown a positive impact on banking profitability and stability, suggesting Chinese commercial banks would become more profitable and stable if they adhere to Basel III regulation. Also, Chinese banks should keep a strict control on the lending activity to guarantee the quality of credit assets, so as to reduce the adverse impact from credit risk to the lowest level. This study also signals a warning about the side effect of banking sector development, as it bring about extra unnecessary cost in a more competitive environment. As for the bank size, it appears to be beneficial to the bank profitability because of the effect of scale and scope economy. With regard to the non-interest income rate, it does not present any significant impact on both profitability and stability, this could be attributed to the very limited proportion of non-interest earning assets in the balance sheet of Chinese commercial banks. Finally, concerning the macroeconomic indicator variable, the real GDP growth rate is found to be positively affects banking profitability and stability, confirming the important role of macro condition for banks operation, although the latter’s effect is proved to be very weak.